Механизмы диффузии примесей замещения в α-Ti - Горев, Никита Дмитриевич (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
The formation energies of interstitial and substitutial defects of Fe, Co and Ga in the α-Ti phase are calculated. Estimated values of impurity atomic concentration allow us to conclude that Fe and Co can diffuse within interstitial mechanism, whereas Ga jumps occur via Ti-vacancies. Migration energies for all impurities are discussed.